PARSJAD, il Parco Archeologico dell'Alto Adriatico: un luogo diffuso, unito dalla tecnologia - Buniotto, Emilia; Alecce, Claudia (Archeomatica, 2014)
Eight partners, coordinated by the Veneto Region, are working on an ambitious project with an innovative approach and tools, and with the ability to conserve content and exploit the immense archaeological heritage of the area concerned. This was the birth of the Parco Archeologico dell'Alto Adriatico (Upper Adriatic Archaeological Park), a project funded by the Italy"Slovenia 2007-2013 Cooperation Programme, with the aim of tracing a unified and cross-border pathof knowledge running from the coast of Emilia to the one in Slovenia.